Возраст щелочно-ультраосновных пород Болярковской интрузии (северо-западная часть Украинского щита) - Цымбал, С.Н.; Степанюк, Л.М.; Цымбал, Ю.С.; Гейко, Ю.В. (Мінералогічний журнал, 2011)
Щелочно-ультраосновные породы Болярковской интрузии по составу соответствуют оливиновым мельтейгитам, ийолитам и якупирангитам и относятся к гипабиссальной фации. Возраст циркона из этих пород составляет 2023—2046 млн лет (U-Pb метод), а позднемагматических амфиболов промежуточного состава между гастингситом и эденитом — 2000 ± 25 млн лет (K-Ar метод). Лужно-ультраосновні породи Болярківської інтрузії за складом відповідають переважно олівіновим мельтейгітам і, частково, ійолітам та якупірангітам і належать до гіпабісальної фації. Вік цирконів із цих порід становить 2023—2046 млн рр. (U-Pb метод), а піз ньомагматичних амфіболів проміжного складу між гастингситом і еденітом — 2000 ± 25 млн рр. (K-Ar метод). Intrusion is located within the Volyn megablock of the Ukrainian Shield. It is located near the junction of intersection of two deep-mantle faults — north-west Sarny- Varvarov and north-east Bolyarka strikes. Intrusion is a steeply dipping dike of capacity about 10 m, composed of melanocratic melteigite, ijolite and jakupirangite. Host rocks are presented by biotite-microcline-plagioclase granite of Paleoproterozoic. On the contact of intrusion granites are significantly fenitizted. A dating of alkalineultrabasic rocks by U-Pb method on zircon and accessory K-Ar method on late-magmatic rock-forming amphibole. The age of zircon calculated by relation ²⁰⁷Pb/²⁰⁶Pb is 2023, 2029 and 2046 Ma on three definitions. Isotopic ages of hastingsite-edenite amphibole of early generation is 2000 ± 25 Ma, and edenite-rihterite amphibole of late generation is 1885 ± 40 Ma. Intrusion is of mantle-derived origin. This is confirmed by findings in its rocks xenokrystes of pyrope, chromite, chromdiopside, enstatite and forsterite with composition of which is close to minerals of the same name from xenoliths of chromshpinel-pyrope dunites, harzburgites and lherzolites in kimberlites.